Successful embolectomy of bilateral femoral artery thrombosis in neonate - Gautam, Bishal; Mathur, R. M.; Devgarha, Sanjeev; Sisodiya, Anula (International Surgery Journal, 2017)
In childhood, the incidence of thrombotic disease, both spontaneous and catheter-induced, is highest in the neonatal period. Depending on the thrombus location, degree of aortic occlusion and involvement of other organs, aortic thrombosis clinical signs range from a completely asymptomatic presentation to a life threatening neonatal emergency. We report a case of aortoiliac thrombosis in a 12 days old baby, who presented with complaints of bluish-black patches on right foot for 4 days. Lower limb CT (Computed Tomography) Angiography showed thrombus in abdominal aorta involving proximal part of right common iliac artery. The anticoagulant therapy was initiated and surgical embolectomy was performed with restoration of blood flow, but the patient developed gangrene of right foot during the follow up period.